2004
DOI: 10.1002/glia.20119
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of the astrocytic glutamate transporter GLT‐1 in the prefrontal cortex of schizophrenics

Abstract: To verify whether altered glial glutamate uptake contributes to the reduced efficacy of glutamatergic transmission reported in the prefrontal cortex of schizophrenics, we studied the expression of GLT-1, the transporter responsible for most glutamate transport, in autoptic samples of prefrontal cortex using real time quantitative RT-PCR, immunocytochemistry, and functional assays. GLT-1 mRNA levels in medication-free patients were 2.5-fold higher than in controls, whereas they were normal or reduced in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(67 citation statements)
references
References 19 publications
2
64
0
1
Order By: Relevance
“…Interestingly, synaptosomal liberation of glutamate was reduced in schizophrenic brain (Sherman et al 1991). An additional mechanistic basis for a reduction in extracellular glutamate levels was recently provided by an elegant study of Matute et al (2005). They showed that levels of both the mRNA and the protein for glial EAAT1 are elevated in the frontal cortex of schizophrenics and also that these transporters display a marked (fourfold) increase in functional activity.…”
Section: Alterations In Endogenous Ligands Of Nmda Receptors In Schizmentioning
confidence: 98%
“…Interestingly, synaptosomal liberation of glutamate was reduced in schizophrenic brain (Sherman et al 1991). An additional mechanistic basis for a reduction in extracellular glutamate levels was recently provided by an elegant study of Matute et al (2005). They showed that levels of both the mRNA and the protein for glial EAAT1 are elevated in the frontal cortex of schizophrenics and also that these transporters display a marked (fourfold) increase in functional activity.…”
Section: Alterations In Endogenous Ligands Of Nmda Receptors In Schizmentioning
confidence: 98%
“…A deficient uptake has been implicated in the pathogenesis of ischemic brain damage [Kuwahara et al, 1992] and may be involved in pathogenesis of neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS) [Rothstein et al, 1995]. Recently, significant increases of mRNA expression of EAAT1 in the thalamus, and EAAT2 in the thalamus and the prefrontal cortex have been reported in schizophrenics, suggesting a possibility that an excessive glutamate uptake is involved in schizophrenia [Smith et al, 2001;Matute et al, 2005]. This possibility was also suggested by the demonstration that the chronic treatment with antipsychotic clozapine reduces glutamate uptake mediated by GLT-1 (EAAT2) in the rat frontal cortex, thereby raising extracellular glutamate levels [Melone et al, 2001[Melone et al, , 2003].…”
mentioning
confidence: 99%
“…Однако при изуче-нии экспрессии мРНК для EAAT2 в префронтальной коре при шизофрении были получены достаточно противоре-чивые данные: как повышение экспрессии указанного транспортера [29,30], так и его снижение [31], а также от-сутствие достоверных изменений [32]. Однако большин-ство авторов полагают, что изменения собственно актив-ности астроцитарных переносчиков могут быть связаны с посттранскрипционным уровнем регуляции.…”
Section: роль астроцитов в нарушениях обратного захвата синаптическогunclassified